Ionic Liquid Confined in Nafion: Toward Molecular‐Level Understanding. Issue 7 (19th February 2013) - Sun, Delin; Zhou, Jian
<x xml:space="preserve">Abstract</x> In this article, multiscale simulation methods were used to study structural and transport properties of Nafion–ionic liquid composite membranes that are novel proton conducting materials for fuel cells. Coarse‐grained model for 1‐butyl‐3‐methylimidazolium tetrafluoroborate ([bmim][BF4]) ionic liquid was first developed in the framework of BMW‐MARTINI force field. Coarse‐grained simulation results of bulk [bmim][BF4] ionic liquid show good agreement with all‐atom simulation results and experimental data. Nafion–[bmim][BF4] composite membranes were then simulated using all‐atom and coarse‐grained models. Ionic liquid cluster formation inside Nafion was revealed by coarse‐grained simulations. Diffusion coefficients of both [bmim]+ cations and <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg2243f4pt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />BF4− anions are reduced by one to two orders of magnitude depending on their concentrations in Nafion membrane. [Bmim]+ cations have faster self‐diffusion coefficient than <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg2243f52d" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />BF4− anions, while this phenomenon is more pronounced when ionic liquids are confined in Nafion. This work provides molecular basis for understanding Nafion–ionic liquid composite membranes. © 2013 American Institute of Chemical Engineers AIChE J, 59: 2630–2639, 2013